(untitled) (Medico Legal Update, 2021)
The essence of the main duties of a judge is to receive, examine, try and decide cases submitted to court. In carrying out their duties, they often face concrete events that must be decided, while the existing laws and regulations are not necessarily complete and clear. Therefore, judges in deciding cases can carry out rechtsvinding. Legal finding (rechtsvinding) is also an important component in landmark decisions because it is related to the breakthroughs made by judges in carrying out their duties. In the perspective of judicial activism, rechtsvinding and landmark decisions are closely related because in practice they can significantly change the existing norms in modern law.